Analysis of Segmenting, Targeting And Positioning At The Cikujang Tapioca Factory Cibugel Sumedang - Helles Amanda; Kokom Komalasari (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
This type of research uses qualitative research with a descriptive approach. Data collection techniques are observation, interviews and documentation as well as data analysis carried out using data reduction, data presentation and drawing conclusions. The results of this study indicate that in terms of market segmentation, the main supply of production is sent to Tasikmalaya and market segmentation covers all segments. Likewise, the target market that maintains product quality can be said to be good compared to other similar products, although the price is slightly higher, but it is comparable to the existing quality. Judging from the Positioning strategy carried out, it is known from the attributes and benefits that product reliability can last long enough. While the benefits offered are that tapioca flour can be processed into a variety of daily food ingredients. Efforts to overcome problems, including expanding marketing reach to other areas to increase product sales turnover, improving product quality in order to maintain customer trust and satisfaction, establishing cooperation with banks for additional capital.